2017
DOI: 10.1002/esp.4173
|View full text |Cite
|
Sign up to set email alerts
|

Meltwater erosion process of frozen soil as affected by thawed depth under concentrated flow in high altitude and cold regions

Abstract: Changes in thawed depth of frozen soil caused by diurnal and seasonal temperature fluctuations are commonly found in high altitude and latitude regions of the world. These changes significantly influence hydrologic and erosion processes. Experimental data are necessary to improve the understanding and modeling of the phenomenon. Laboratory experiments were conducted in Beijing to assess the impacts of thawed soil depth, slope gradient, and flow rate on soil erosion by concentrated meltwater flow over an underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…The snow-thaw runoff of diurnal and seasonal permafrost is the main geomorphic agent in cold, high-latitude and high-altitude regions [1][2][3][4]. Seasonal fluctuations in circulation and temperature lead to daily fluctuations in soil, resulting in the thawing of permafrost and ice, which can significantly alter soil erosion [5].…”
Section: Introductionmentioning
confidence: 99%
“…The snow-thaw runoff of diurnal and seasonal permafrost is the main geomorphic agent in cold, high-latitude and high-altitude regions [1][2][3][4]. Seasonal fluctuations in circulation and temperature lead to daily fluctuations in soil, resulting in the thawing of permafrost and ice, which can significantly alter soil erosion [5].…”
Section: Introductionmentioning
confidence: 99%
“…These intensive human activities have greatly altered the geomorphology and hydrology of the landscape. Previous studies have focused on the effect of land use change (e.g., converting cropland into forest and grassland and sealing off mountainous areas for afforestation) on the k (Fang, ; Ouyang et al, ), the assessment of particular regions (e.g., the Tibetan Plateau, the Loess Plateau, and Karst geomorphology; Ban et al, ; Sun et al, ; Wang & Li, ; Zeng et al, ), mapping (Yao et al, ), and the relationships between the k and soil microbial properties (Gao et al, ; Zhang et al, ). In addition, some studies have used the RUSLE model to calculate the loss due to soil erosion (Feng et al, ; Liu & Fu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al (2015) studied the impacts of FT cycles on runoff and sediment yield of slope land and found that FT cycles greatly increased the sediment yield intensity. In contrast, Ban et al (2017) found that shallower thawed depths delivered more sediments than deeper thawed depths of high altitude and latitude regions. However, few studies have investigated the effects of thawed depth on soil erosion processes in loess slopes under simulated rainfall.…”
Section: Introductionmentioning
confidence: 75%
“…Zhang et al (2015) found that the critical shear stress was 12.8 Pa under a steep slope accumulation yield experiment (30∼50 • ), while we found that critical shear stress was almost 20 times greater than that obtained in their study at 15 • . Together, these results suggest that FTed soil has a greater erodibility and is less resistant to erosion (Li and Fan, 2014;Ban et al, 2017;Wang et al, 2020).…”
Section: Response Of Soil Loss Rate To Hydraulics Conditionsmentioning
confidence: 86%